1994
DOI: 10.1128/jb.176.8.2300-2307.1994
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Escherichia coli hydroperoxidase I by acetate and other weak acids

Abstract: Escherichia coli produces two independently regulated hydroperoxidases (catalases) that protect the cell from toxic concentrations of hydrogen peroxide. Hydroperoxidase I (HPI) is induced by hydrogen peroxide in an OxyR-dependent manner, while hydroperoxidase II (HPII) synthesis is regulated by an alternative sigma factor called RpoS (KatF). The activities of both hydroperoxidases increase as exponentially growing cells enter stationary phase. In this study, we examined the growth phase-dependent expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 33 publications
1
40
1
Order By: Relevance
“…The factor(s) responsible for this repression, and the repression of the promoter at elevated temperatures, have not been identified. In E. coli, treatment with 5n7 mM ascorbic acid results in an eightfold increase in catalase activity (Richter & Loewen, 1981), while treatment with 0-80 mM sodium acetate (pH 7n0) induces catalase activity sevenfold (Mukhopadhyay & Schellhorn, 1994). The treatment of M. smegmatis\pK20 with 10 mM ascorbic acid, however, resulted in less than twofold induction of the M. tuberculosis katG promoter, while no induction was observed in response to sodium acetate.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The factor(s) responsible for this repression, and the repression of the promoter at elevated temperatures, have not been identified. In E. coli, treatment with 5n7 mM ascorbic acid results in an eightfold increase in catalase activity (Richter & Loewen, 1981), while treatment with 0-80 mM sodium acetate (pH 7n0) induces catalase activity sevenfold (Mukhopadhyay & Schellhorn, 1994). The treatment of M. smegmatis\pK20 with 10 mM ascorbic acid, however, resulted in less than twofold induction of the M. tuberculosis katG promoter, while no induction was observed in response to sodium acetate.…”
Section: Discussionmentioning
confidence: 89%
“…E. coli promoters which deviate in this position generally require activators for efficient transcription initiation. These activators normally bind to sites at various distances upstream of the k35 region (Raibaud & Schwartz, 1984 ;Zhou et al, 1994a, b (Mukhopadhyay & Schellhorn, 1994 ;Rocha & Smith, 1995 ;Schnell & Steinman, 1995). In E. coli, the induction of katG as the cells enter stationary phase is dependent on the stationary-phase or starvation response σ factor, KatF or RpoS (Loewen et al, 1985 ;Mulvey et al, 1988 ;Mukhopadhyay & Schellhorn, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that in the stationary phase HPI is partially induced by S in E. coli (8,24) and in the exponential phase some virulence genes are regulated by S in Salmonella dublin (5), exponential-phase induction of HPI by S has not been examined previously. In the present study, however, we found that in V. vulnificus this global regulator plays a role in the response to oxidative stress during the exponential phase by increasing the amount of HPI with no involvement of HPII.…”
Section: Resultsmentioning
confidence: 99%
“…(39,42,43) and a repressor, repressing its own expression (10) and that of the mom gene of phage Mu (6). Since the role of OxyR has been studied using exponential-phase cultures (10,28,29) and the differences in expression of the hps::lacZ fusions in overnight cultures were modest between oxyR ϩ and ⌬oxyR backgrounds for most fusions (Table 3), we decided to study the expression of the hps::lacZ fusions in isogenic oxyR ϩ and ⌬oxyR backgrounds during normal growth to determine which of these hps loci are activated or repressed by OxyR. Each of these hps::lacZ operon fusions showed individual variable expression patterns during growth, indicating that each fusion is unique in its regulation.…”
Section: Resultsmentioning
confidence: 99%